Working with robotic process automation: User experience after 18 months of adoption - Filgueiras, Lucia Vilela Leite; Corrêa, Pedro Luiz Pizzigatti; Alves-Souza, Solange N.; Teodoro, Sigmar Monroe; Silva, Mariana Savarezze Pereira da; Encinas Quille, Rosa Virginia; Demuner, Vanessa Rafaela de Souza (Frontiers in Computer Science, 2022)
This paper reports a study of User Experience (UX) with Robotic Process Automation (RPA), in the perspective of workers of EdP Brazil, a large electric utility company that operates in Brazil. RPA are software solutions for automating business processes that find increased interest of companies because they are inserted in workgroups as a co-worker, emulating human workers operating on GUI interfaces. Although the technology promises to drive a new wave of productivity in service companies, its impact on co-workers’ experience is still unexplored. Based on projective interviews using the AXE (Anticipated eXperience Evaluation) protocol, after the first 18 months of RPA operation, the analysis of workers’ collaboration with the robots has evidenced multiple facets of UX, technology acceptance and innovation adoption. For this case, RPA has provided an overall positive user experience mainly due to the perceived utility of the spared time, the upgrade in career opportunities and the pride for actively participating in the innovation adoption. Negative experience comes mainly from the lack of visibility that hinders robot management for efficiency and improvement. The methodology used in the study was successful in capturing the multifaceted workers’ experience and is potentially useful to support user research in new expansion RPA projects.